Positive electrode material, preparation method thereof and sodium ion battery
Through the improved co-precipitation method, Na2-xFeFe(CN)6 positive electrode material was synthesized and combined with molybdenum disulfide/azepylated graphene, the problem of poor circulation performance of the positive electrode material of sodium ion battery was solved, and high specific capacity and excellent electricity were achieved Chemical properties.
Patent Information
- Application Number
- CN202411402954.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2025-02-18
AI Technical Summary
The cycling performance of the positive electrode material of sodium ion battery is poor and sensitive to moisture and temperature conditions, and there are problems such as high crystal water content and structural defects.
The modified co-precipitation method was used to synthesize the Na2-xFeFe(CN)6 positive electrode material with a highly reversible rhombic structure, and the molybdenum disulfide/azepylated graphene was combined on its surface, and the material structure was adjusted by controlling the precipitation process and adding additives. performance.
The circulation performance, rate performance and electrochemical performance of the positive electrode material of sodium ion battery are improved, the crystal water content is reduced, the chemical stability is enhanced, and the specific capacity is improved.
Smart Images

Figure BDA0005075767240000091
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of battery materials, and in particular relates to a positive electrode material and a preparation method thereof, and a sodium ion battery. Background Art
[0002] Due to the low cost and high natural reserves of sodium, sodium-ion batteries are considered to be an alternative to lithium-ion batteries and are expected to be used in large-scale energy storage in the future. Different cathode materials used in sodium-ion batteries include layered oxides, polyanionic compounds, and Prussian blue analogs. Among them, Prussian blue analogs can easily accommodate Na due to their open framework structure. + Compared with other cathode materials, Prussian blue analogs have large sodium ion migration channels, high specific capacity, and do not require high-temperature calcination during the synthesis process, which effectively reduces the manufacturing cost; however, this type of material is sensitive to moisture and temperature conditions and needs to be prepared under low humidity conditions. The product crystal structure is prone to defects and easy to carry crystal water. In the actual production and application process, it is necessary to overcome the problems of limited cycle life and narrow operating temperature range.
[0003] Prussian blue sodium ion battery positive electrode materials can be synthesized by thermal decomposition, hydrothermal method and coprecipitation method. Among them, coprecipitation method is a green and environmentally friendly method that can achieve scaled-up production. Patent application with publication number CN107364875A discloses a method for preparing Prussian blue positive electrode materials and sodium ion batteries, and patent application with publication number CN106745068A discloses a method for preparing low-defect nano Prussian blue and its application. However, the above synthesis method simply mixes transition metal salts and sodium ferrocyanide solutions, and the reaction rate is difficult to control, resulting in poor crystallinity of the material, low sodium content, and still high moisture content in the material, poor electrochemical performance, poor cycle performance, and low chemical stability, which in turn affects practical applications.
[0004] Adding surfactants, chelating agents, etc. to the coprecipitation reaction system can regulate the crystallization rate, thereby reducing the vacancies and crystal water content in the structure and increasing the sodium content to obtain excellent electrochemical performance. However, this method uses more additives, which increases the synthesis cost. The residues on the crystal surface and the experimental additives also have a certain impact on the environment. Summary of the invention
[0005] The object of the present invention is to provide a positive electrode material and a preparation method thereof, and a sodium ion battery, so as to solve the problem of poor cycle performance of the positive electrode material of the sodium ion battery.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] A positive electrode material comprising Na2-x FeFe(CN)6 and molybdenum disulfide / nitrogen hybridized graphene; wherein x=0-2.
[0008] Furthermore, the Na 2-x The mass ratio of FeFe(CN)6 and molybdenum disulfide / nitrogen-hybridized graphene is 85-95:5-15.
[0009] Furthermore, the Na 2-x FeFe(CN)6 is prepared by the following steps:
[0010] Sodium citrate and FeSO4·7H2O were dissolved in deionized water to form a mixed solution, stirred, and then sodium citrate and Na4Fe(CN)6·10H2O were dissolved in deionized water to form a dispersion solution, stirred, and the mixed solution was added dropwise to the dispersion solution under N2 protection, stirred at room temperature, centrifuged, washed, and dried to obtain Na 2-x FeFe(CN)6.
[0011] Furthermore, the dosage ratio of sodium citrate, FeSO4·7H2O and deionized water in the mixed solution is 3-7 g: 2-2.2 g: 100-120 mL, and the stirring time is 2-3 h.
[0012] Furthermore, the dosage ratio of sodium citrate, Na4Fe(CN)6·10H2O and deionized water in the dispersion is 3-7 g: 2.5-2.8 g: 100-120 mL, and the stirring time is 2-3 h.
[0013] Furthermore, the room temperature stirring is stirring at 800-900 rpm for 6-8 hours.
[0014] Furthermore, the drying is carried out in a vacuum oven at 110-120° C. for 12-14 hours.
[0015] Furthermore, the molybdenum disulfide / nitrogen-hybridized graphene is prepared by the following steps:
[0016] Add 50% CH2N2 by mass to a 1.2 mg / mL graphene oxide aqueous solution, stir for 2 to 2.5 hours, place in a reactor, react at 170 to 180°C for 12 to 14 hours, cool to room temperature, and obtain nitrogen-doped graphene gel; finally, heat the dried graphene gel to 1000 to 1050°C in a high-purity argon atmosphere and keep warm for 3 to 4 hours, and cool naturally to obtain nitrogen-doped graphene;
[0017] Ammonium tetrathiomolybdate and nitrogen-doped graphene are dissolved in deionized water and stirred evenly. The mixed solution is then transferred to a reactor and reacted at 210-220° C. for 12-14 hours. The mixture is cooled to room temperature, washed and dried to obtain molybdenum disulfide / nitrogen-doped graphene.
[0018] Furthermore, the dosage ratio of the CH2N2 and graphene oxide solution is 10-12 mL: 100-110 mL.
[0019] Furthermore, the usage ratio of the ammonium tetrathiomolybdate, nitrogen-doped graphene and deionized water is 0.5-0.7 g: 0.15-0.2 g: 150-180 mL.
[0020] A method for preparing a positive electrode material comprises the following steps:
[0021] Will Na 2-x FeFe(CN)6 and molybdenum disulfide / nitrogen-doped graphene were dissolved in ethanol and stirred evenly to obtain a mixed solution; the mixed solution was spray dried by a spray dryer while continuing to stir, and Na 2-x FeFe(CN)6@MoS2 / N-hybridized graphene cathode material.
[0022] Furthermore, the Na 2-x The dosage ratio of FeFe(CN)6, molybdenum disulfide / nitrogen-hybridized graphene and ethanol is 85-95g:5-15g:420-450mL; the stirring time is 2-4h.
[0023] Furthermore, the feed temperature of the spray dryer is set to 180-210° C., the outlet temperature is set to 120-150° C., and the feed rate is 60-90 mL / h.
[0024] A sodium ion battery comprises a positive electrode, wherein the positive electrode comprises any one of the positive electrode materials described above.
[0025] Beneficial effects of the present invention:
[0026] (1) The sodium-rich Prussian blue analog (Na 2-x FeFe(CN)6), [Fe(CN)6] 4- The high-spin Fe and low-spin Fe in the group are linked to N and C atoms respectively to form an open three-dimensional framework structure with high specific capacity but high crystal water content. By controlling the precipitation process, the prepared Na 2- x The FeFe(CN)6 rhombohedral structure is highly reversible and reduces the crystal water content. + Ion in and out, Na 2-xFeFe(CN)6 undergoes three-phase transitions between rhombus, cubic, and tetrahedron; the structure is stable and exhibits excellent rate performance, cycling performance, and electrochemical performance.
[0027] (2) The present invention uses molybdenum disulfide / nitrogen-hybridized graphene combined with Na 2-x FeFe(CN)6 outer layer, nitrogen-doped graphene has higher specific capacity and chemical stability than graphene. MoS2 has high theoretical specific capacity and moderate voltage platform. Its special layered structure provides Na + The convenient transport within the lattice promotes the electrode reaction process of sodium insertion and extraction; nitrogen-doped graphene and molybdenum disulfide are combined and combined with Na 2-x FeFe(CN)6 surface, excellent chemical stability makes up for the Na 2-x The lack of stability of FeFe(CN)6 improves the specific capacity and cyclability of sodium-ion batteries. DETAILED DESCRIPTION
[0028] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] Example 1
[0030] This embodiment provides a sodium ion battery, which is prepared by the following steps:
[0031] In the first step, 7g sodium citrate and 2g FeSO4·7H2O were dissolved in deionized water to form a mixed solution, and the mixture was stirred for 3h. Then, 7g sodium citrate and 2.5g Na4Fe(CN)6·10H2O were dissolved in deionized water to form a dispersion solution, and the mixture was stirred for 3h. The mixture was added dropwise to the dispersion solution under N2 protection, and the mixture was stirred at 900rpm for 6h, and then centrifuged for washing. The mixture was dried in a vacuum oven at 110℃ for 14h to obtain Na 2-x FeFe(CN)6.
[0032] In the second step, 10 mL of 50% CH2N2 was added to 100 mL of 1.2 mg / mL graphene oxide aqueous solution, stirred for 2.5 h, placed in a reactor, reacted at 170°C for 14 h, cooled to room temperature, and nitrogen-doped graphene gel was obtained; finally, in a high-purity argon atmosphere, the dried graphene gel was heated to 1000°C and kept warm for 4 h, and naturally cooled to obtain nitrogen-doped graphene.
[0033] 0.6 g of ammonium tetrathiomolybdate and 0.2 g of nitrogen-doped graphene were dissolved in 160 mL of deionized water and stirred evenly, and then the mixed solution was transferred to a reactor and reacted at 210° C. for 12 h. Cooled to room temperature, washed and dried to obtain molybdenum disulfide / nitrogen-doped graphene.
[0034] Step 3: 95g Na 2-x FeFe(CN)6 and 5 g of molybdenum disulfide / nitrogen-hybridized graphene were dissolved in 420 mL of ethanol and stirred evenly to obtain a mixed solution; the mixed solution was spray dried by a spray dryer with continuous stirring, the feed temperature of the spray dryer was set to 210 ° C, the outlet temperature was set to 140 ° C, and the feed rate was 70 mL / h to obtain Na 2-x FeFe(CN)6@MoS2 / N-hybridized graphene cathode material.
[0035] Step 4: Na 2-x FeFe(CN)6@molybdenum disulfide / nitrogen hybridized graphene positive electrode material, conductive agent, and binder are mixed in a mass ratio of 8:1:1, added to N-methylpyrrolidone, stirred evenly to obtain positive electrode slurry, and then coated on the positive electrode current collector aluminum foil, and punched into a positive electrode with a diameter of 14 mm after drying at 80°C; the negative electrode is directly selected from a metal sodium sheet; in an argon atmosphere glove box, NaClO4 is dissolved in a mixed organic solvent of propylene carbonate and ethylene carbonate in a volume ratio of 1:1 to obtain an electrolyte, wherein the concentration of NaClO4 is 1 mol / L; a polypropylene film is used as an isolation membrane;
[0036] Place the positive electrode, separator, and negative electrode in order, inject the prepared electrolyte into the dried battery cell, and assemble it into a button battery.
[0037] Example 2
[0038] The present embodiment is different from the embodiment 1 in that the “7 g sodium citrate” in the mixed solution and the dispersion in the first step is changed to “5 g sodium citrate”.
[0039] The remaining raw materials and preparation process remain the same as in Example 1.
[0040] Example 3
[0041] The present embodiment is different from the embodiment 1 in that the “7 g sodium citrate” in the mixed solution and the dispersion in the first step is changed to “3 g sodium citrate”.
[0042] The remaining raw materials and preparation process remain the same as in Example 1.
[0043] Example 4
[0044] The difference between this embodiment and embodiment 1 is that in the third step, "95g Na2-x FeFe(CN)6 and 5g MoS2 / N-hybridized graphene" was changed to "85g Na 2-x FeFe(CN)6 and 15g MoS2 / N-hybridized graphene".
[0045] The remaining raw materials and preparation process remain the same as in Example 1.
[0046] Example 5
[0047] The present embodiment is different from the embodiment 1 in that in the third step, "the feeding rate is 70 mL / h" is changed to "the feeding rate is 90 mL / h".
[0048] The remaining raw materials and preparation process remain the same as in Example 1.
[0049] Comparative Example 1
[0050] This comparative example is different from Example 1 in that N2 is not passed in the first step. The specific implementation steps are as follows:
[0051] In the first step, 7g sodium citrate and 2g FeSO4·7H2O were dissolved in deionized water to form a mixed solution, and the mixture was stirred for 3h. Then, 7g sodium citrate and 2.5g Na4Fe(CN)6·10H2O were dissolved in deionized water to form a dispersion solution, and the mixture was stirred for 3h. The mixture was added dropwise to the dispersion solution under N2 protection, and the mixture was stirred at 900rpm for 6h, and then centrifuged for washing. The mixture was dried in a vacuum oven at 110℃ for 14h to obtain Na 2-x FeFe(CN)6.
[0052] The remaining raw materials and preparation process remain the same as in Example 1.
[0053] Comparative Example 2
[0054] The difference between this comparative example and Example 1 is that no sodium citrate is added to the dispersion.
[0055] The remaining raw materials and preparation process remain the same as in Example 1.
[0056] Comparative Example 3
[0057] Compared with Example 1, this comparative example differs in that, in the second step, the molybdenum disulfide component is removed, and the specific implementation steps are as follows:
[0058] In the second step, 10 mL of 50% CH2N2 was added to 100 mL of 1.2 mg / mL graphene oxide aqueous solution, stirred for 2.5 h, placed in a reactor, reacted at 170°C for 14 h, cooled to room temperature, and nitrogen-doped graphene gel was obtained; finally, in a high-purity argon atmosphere, the dried graphene gel was heated to 1000°C and kept warm for 4 h, and naturally cooled to obtain nitrogen-doped graphene.
[0059] The remaining raw materials and preparation process remain the same as in Example 1.
[0060] Comparative Example 4
[0061] Compared with Example 1, the difference between this comparative example is that the spray drying operation in the third step is changed to drying, and the specific implementation steps are as follows:
[0062] Step 3: 95g Na 2-x FeFe(CN)6 and 5 g of molybdenum disulfide / nitrogen-doped graphene were dissolved in 420 mL of ethanol and stirred evenly to obtain a mixed solution, which was then dried at 70 °C to obtain Na 2-x FeFe(CN)6@MoS2 / N-hybridized graphene cathode material.
[0063] The remaining raw materials and preparation process remain the same as in Example 1.
[0064] Comparative Example 5
[0065] Compared with Example 1, this comparative example is different in that the second to third steps are removed, and the specific implementation operations are as follows:
[0066] In the first step, 7g sodium citrate and 2g FeSO4·7H2O were dissolved in deionized water to form a mixed solution, and the mixture was stirred for 3h. Then, 7g sodium citrate and 2.5g Na4Fe(CN)6·10H2O were dissolved in deionized water to form a dispersion solution, and the mixture was stirred for 3h. The mixture was added dropwise to the dispersion solution under N2 protection, and the mixture was stirred at 900rpm for 6h, and then centrifuged for washing. The mixture was dried in a vacuum oven at 110℃ for 14h to obtain Na 2-x FeFe(CN)6.
[0067] The second step is to 2-xFeFe(CN)6 positive electrode material, conductive agent and binder are mixed in a mass ratio of 8:1:1, added to N-methylpyrrolidone, stirred evenly to obtain positive electrode slurry, and then coated on the positive electrode current collector aluminum foil, and punched into a positive electrode with a diameter of 14 mm after drying at 80°C; the negative electrode is directly selected from a metal sodium sheet; in an argon atmosphere glove box, NaClO4 is dissolved in a mixed organic solvent of propylene carbonate and ethylene carbonate in a volume ratio of 1:1 to obtain an electrolyte, wherein the concentration of NaClO4 is 1 mol / L; a polypropylene film is used as an isolation membrane;
[0068] Place the positive electrode, separator, and negative electrode in order, inject the prepared electrolyte into the dried battery cell, and assemble it into a button battery.
[0069] The remaining raw materials and preparation process remain the same as in Example 1.
[0070] Comparative Example 6
[0071] Compared with Example 1, this comparative example differs in that "nitrogen-hybridized graphene" is replaced with "graphene", and the specific implementation steps are as follows:
[0072] In the first step, 7g sodium citrate and 2g FeSO4·7H2O were dissolved in deionized water to form a mixed solution, and the mixture was stirred for 3h. Then, 7g sodium citrate and 2.5g Na4Fe(CN)6·10H2O were dissolved in deionized water to form a dispersion solution, and the mixture was stirred for 3h. The mixture was added dropwise to the dispersion solution under N2 protection, and the mixture was stirred at 900rpm for 6h, and then centrifuged for washing. The mixture was dried in a vacuum oven at 110℃ for 14h to obtain Na 2-x FeFe(CN)6.
[0073] In the second step, 0.6 g of ammonium tetrathiomolybdate and 0.2 g of graphene were dissolved in 160 mL of deionized water and stirred evenly, and then the mixed solution was transferred to a reactor and reacted at 210° C. for 12 h. The mixture was cooled to room temperature, washed and dried to obtain molybdenum disulfide / graphene.
[0074] Step 3: 95g Na 2-x FeFe(CN)6 and 5g molybdenum disulfide / graphene were dissolved in 420mL ethanol and stirred evenly to obtain a mixed solution; the mixed solution was spray dried by a spray dryer with the feed temperature of the spray dryer set to 210℃, the outlet temperature set to 140℃, and the feed rate set to 70mL / h to obtain Na 2-x FeFe(CN)6@MoS2 / graphene positive electrode material.
[0075] Step 4: Na 2-xFeFe(CN)6@molybdenum disulfide / graphene positive electrode material, conductive agent, and binder are mixed in a mass ratio of 8:1:1, added to N-methylpyrrolidone, stirred evenly to obtain positive electrode slurry, and then coated on the positive electrode current collector aluminum foil, and punched into a positive electrode with a diameter of 14 mm after drying at 80°C; the negative electrode is directly selected from the metal sodium sheet; in an argon atmosphere glove box, NaClO4 is dissolved in a mixed organic solvent of propylene carbonate and ethylene carbonate in a volume ratio of 1:1 to obtain an electrolyte, wherein the concentration of NaClO4 is 1 mol / L; a polypropylene film is used as an isolation membrane;
[0076] Place the positive electrode, separator, and negative electrode in order, inject the prepared electrolyte into the dried battery cell, and assemble it into a button battery.
[0077] The remaining raw materials and preparation process remain the same as in Example 1.
[0078] The performance tests were performed on Examples 1 to 5 and Comparative Examples 1 to 6.
[0079] The sodium ion batteries obtained in various embodiments and comparative examples of the present application were subjected to 50 cycle performance tests at a current of 0.1C and a voltage of 2.0-4.0V on a battery tester;
[0080] The results are shown in Table 1:
[0081] Table 1
[0082]
[0083] As can be seen from Table 1, compared with Example 1, Examples 2 to 3 and Comparative Example 2 mainly show a decrease in the first discharge specific capacity. This is because sodium citrate not only acts as a chelating agent in the system, but also supplements sodium ions, and the amount of sodium ions directly affects the specific capacity of the sodium ion battery; compared with Example 1, Example 4 shows that the proportion of materials will affect the final specific capacity and battery cyclability; compared with Example 1, Example 5 shows a decrease in specific capacity. After the rate is increased, the particle size of the final electrode material will increase and the specific surface area will decrease, thereby causing the electrochemical performance of the electrode material to decrease.
[0084] Comparative Example 1 Compared with Example 1, after not introducing N2 protection, Fe 2+ It is easily oxidized by oxygen in the air, resulting in [Fe(CN)6] 4-Compared with Example 1, the specific capacity of Comparative Example 3 is reduced after no addition of molybdenum disulfide, because its special layered structure promotes the electrode reaction process of sodium deintercalation; Compared with Example 1, conventional drying will form particle agglomeration and hardening, which is not conducive to the maintenance of material structure, resulting in a decrease in specific capacity; Compared with Example 1, Comparative Example 5 will cause Na 2-x The FeFe(CN)6 structure is unstable. In addition, molybdenum disulfide / nitrogen-hybridized graphene can improve the dielectric properties of the overall material, thereby improving the specific capacity. Compared with Example 1, the difference in Comparative Example 6 is that the graphene is nitrogen-doped. The nitrogen-doped graphene has a large number of pore structures, which can provide sufficient positions to facilitate the adsorption of ions and accelerate electron transfer. In addition, the nitrogen molecular groups are covalently bonded to provide stability.
[0085] In summary, the sodium ion battery provided by the present invention using the positive electrode material prepared by the preparation method has the characteristics of high specific capacity and strong cycle performance, and provides a good idea and method for designing and producing high-performance sodium ion batteries.
[0086] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0087] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A positive electrode material, characterized in that: Including Na 2-x FeFe(CN)6 and molybdenum disulfide / nitrogen hybridized graphene; wherein x=0-2.
2. A positive electrode material according to claim 1, characterized in that: The Na 2-x The mass ratio of FeFe(CN)6 and molybdenum disulfide / nitrogen-hybridized graphene is 85-95:5-15.
3. A positive electrode material according to claim 1, characterized in that: The Na 2-x FeFe(CN)6 is prepared by the following steps: Sodium citrate and FeSO4·7H2O were dissolved in deionized water to form a mixed solution, stirred, and then sodium citrate and Na4Fe(CN)6·10H2O were dissolved in deionized water to form a dispersion solution, stirred, and the mixed solution was added dropwise to the dispersion solution under N2 protection, stirred at room temperature, centrifuged, washed, and dried to obtain Na 2-x FeFe(CN)6.
4. A positive electrode material according to claim 3, characterized in that: The dosage ratio of sodium citrate, FeSO4·7H2O and deionized water in the mixed solution is 3-7g: 2-2.2g: 100-120mL, and the stirring time is 2-3h; the dosage ratio of sodium citrate, Na4Fe(CN)6·10H2O and deionized water in the dispersed solution is 3-7g: 2.5-2.8g: 100-120mL, and the stirring time is 2-3h.
5. A positive electrode material according to claim 3, characterized in that: The room temperature stirring is stirring at 800-900 rpm for 6-8 hours; the drying is drying in a vacuum oven at 110-120° C. for 12-14 hours.
6. A positive electrode material according to claim 1, characterized in that: The molybdenum disulfide / nitrogen-hybridized graphene is prepared by the following steps: Add 50% CH2N2 by mass to a 1.2 mg / mL graphene oxide aqueous solution, stir for 2 to 2.5 hours, place in a reactor, react at 170 to 180°C for 12 to 14 hours, cool to room temperature, and obtain nitrogen-doped graphene gel; finally, heat the dried graphene gel to 1000 to 1050°C in a high-purity argon atmosphere and keep warm for 3 to 4 hours, and cool naturally to obtain nitrogen-doped graphene; Ammonium tetrathiomolybdate and nitrogen-doped graphene are dissolved in deionized water and stirred evenly. The mixed solution is then transferred to a reactor and reacted at 210-220° C. for 12-14 hours. The mixture is cooled to room temperature, washed and dried to obtain molybdenum disulfide / nitrogen-doped graphene.
7. A positive electrode material according to claim 6, characterized in that: The dosage ratio of the CH2N2 and graphene oxide solution is 10-12 mL: 100-110 mL; the dosage ratio of the ammonium tetrathiomolybdate, nitrogen-doped graphene and deionized water is 0.5-0.7 g: 0.15-0.2 g: 150-180 mL.
8. A method for preparing a positive electrode material according to any one of claims 1 to 7, characterized in that: The following steps are involved: Will Na 2-x FeFe(CN)6 and molybdenum disulfide / nitrogen-doped graphene were dissolved in ethanol and stirred evenly to obtain a mixed solution; the mixed solution was spray dried by a spray dryer while continuing to stir, and Na 2-x FeFe(CN)6@MoS2 / N-hybridized graphene cathode material.
9. The method for preparing a positive electrode material according to claim 8, characterized in that: The stirring time is 2 to 4 hours; the feed temperature of the spray dryer is set to 180 to 210° C., the outlet temperature is set to 120 to 150° C., and the feed rate is 60 to 90 mL / h.
10. A sodium ion battery, characterized in that: It comprises a positive electrode, wherein the positive electrode comprises the positive electrode material according to any one of claims 1 to 7.
Citation Information
Patent Citations
Preparation method of low-defect nano-Prussian blue, and application of nano-Prussian blue
CN106745068A
Method for preparing Prussian blue positive electrode material, and sodium ion battery
CN107364875A
